Physico-Chemical and Magnetic Characterization of Topsoil Influenced by Vehicular Emissions at Padjadjaran University, Jatinangor - Septiani, Fadia Tri; Fitriani, Dini; Agustine, Eleonora; Kirana, Kartika Hajar; Aji, Bayu Gusti Pangestu (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2025)
This study investigates the impact of vehicular emissions on the physico-chemical properties of topsoil at Padjadjaran University, Jatinangor. Soil samples were analyzed for pH, electrical conductivity (EC), total dissolved solids (TDS), magnetic susceptibility ()LFll, magnetic domain properties (), and heavy metal concentrations using Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES). The results showed that while pH values remained within the neutral range (6.03–7.40), elevated EC and TDS values were observed at locations with high traffic density, indicating increased ionic content from anthropogenic sources. Magnetic susceptibility values ranged from 506.7 to 1148.7 × 10⁻⁸ m³kg⁻¹, with all sites exceeding 10 × 10⁻⁸ m³kg⁻¹, confirming the presence of ferrimagnetic minerals, and higher values were found near areas with heavy vehicle activity. The ) values, mostly below 4%, suggest a significant contribution from anthropogenic magnetic particles, dominated by stable single domain (SSD) and multi domain (MD) grains. Heavy metal analysis revealed that most elements (Fe, Mn, Cu, Zn, Al, As, Mg, Ca, K, Ni and Cr) were within permissible limits, except cadmium (Cd), which exceeded background crustal levels, suggesting contamination from anthropogenic sources, including vehicle emissions.